Christology and Philosophical Anthropology: Understanding Human Dignity - María Teresa Lopez; Francisco Rivera; Camila Vargas (International Forum of Researchers and Lecturers, 2024)
This paper explores the intersection of Christology and philosophical anthropology in articulating the concept of human dignity. It examines the theological significance of the Incarnation and its implications for understanding personhood, freedom, and morality in Catholic philosophy. The study also considers how these insights respond to contemporary bioethical and societal challenges.